Analisis Kemampuan Keuangan Daerah Dalam Pelaksanaan Otonomi Daerah Di Kabupaten Merangin - Novia Sartika (Jurnal Dinamika Manajemen, 2016)
This research is entitled Analysis of Regional Financial Capacity in the Implementation of Regional Autonomy in Merangin Regency, under the guidance of Mr. Drs. Adi Bhakti,S.E.,M.si. This study aims to determine and analyze the development of regional own-source revenue (PAD), regional financial capability seen by the degree of fiscal decentralization, regional financial capacity seen by the ratio of self-sufficiency, as well as regional financial routine capabilities in Merangin district. The results of this study show that the development of regional original income in Merangin Regency during the 2007-2011 period showed fluctuating growth. The DDF for Merangin Regency is still on a very low interval scale because it is between 0-10%. As for the independence ratio, it is said to be very low, namely between 0-25%. And for routine ability it is said to be low because it is on a scale of 0-30%. The low routine capacity ratio is said to be low because Merangin Regency during the 2007-2011 period indicates that the regional government is still very dependent on the central government.